MISIOLOGI KONTEKSTUAL DI INDONESIA: SOLUSI TEOLOGIS DAN SOSIAL UNTUK MASYARAKAT PLURALIS - Tonny Andrian; Waharman Waharman (Manna Rafflesia, 2024)
In Indonesia, a pluralistic society with diverse cultures, religions, ethnicities, and worldviews poses significant challenges to church missiology. Horizontal conflicts related to religion and ethnicity are a frequent occurrence in the course of the nation's journey. This article explores the theological and social approaches to dealing with the issue's complexity. It investigates how the church can be a positive change agent in promoting interfaith dialogue, building social harmony, and strengthening cross-cultural understanding. Using a research method that involves theological study and social analysis expressed in a descriptive qualitative method with a literature study approach to understand the church's and missionaries' role in contemporary society. The conclusion is the need for the church to understand the dynamics of pluralism in the context of missiology in Indonesia so that it can provide a theological approach strategy in missiology for multicultural societies and also the importance of social strategies in facing the challenges of missiology in contemporary society. Finally, it can provide social and cultural impacts and implications for the practice of missiology in Indonesia. hence highlighting the need for a holistic approach that integrates theology with the social context of society, so that missiology can play an effective role in facing contemporary challenges and expanding its positive impact in social and spiritual transformation in Indonesia.